Pay Transparency in Organizations - Amir Habibi (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
I study when a firm prefers to be transparent about pay using a simple multidimensional signaling model. Pay transparency within the firm means that a worker can learn about his own worker-firm match from another worker's pay. This can either encourage or discourage workers – which affects retention – and so creates a trade-off for the firm when it commits to a level of transparency. The model pre- dicts that when few workers have a high worker-firm match, transparency is always preferred by the firm and becomes more favorable as the value of retaining these 'star' workers increases. This prediction is consistent with the firms in the field that choose to be internally transparent about pay. The model also predicts that transparency leads to pay compression, again consistent with evidence from the field.
Keywords: D82; D86; J30; M52; 330; pay transparency; bonus pay; multidimensional signaling; relative pay